Modelling and analysis of resource allocation for hospital inpatient operations - Lum, Jocelyn, Wei Xin (2019)
Introduction More patients are opting to go for Same-Day admissions, where they can register and go for their operations with significantly reduced waiting time. The objective of this paper is to find out the optimal schedule (for eight specialty groups for every weekday) to release beds to reduce patient waiting time and maximise bed utilisation.